Geochemical Characterization of the Zinc Element in the Toquepala Mine and its implications in the metallurgical treatment - Cossío Sánchez, Diego (2017)
The investigation based on the implications of zinc in the metallurgical treatment of copper in the Toquepala Mine, present in this type of deposit, was based on the knowledge of the characteristics and geochemical behavior of zinc and Cu-Mo-Fe-As- Pb, starting from the definition of geological domains based on the domains of lithology, alteration, mineralization and presence of gypsum, arriving to determine that the geochemical characteristics are different in each geological domain, being more favorable in the concentration and recovery of copper, domains Geological characteristics of low zinc, iron, arsenic and lead elements, and also with the presence of gypsum / anhydrite contents. The correct determination of the parameters of the descriptive statistics of the elements Zn-Cu-Mo-Fe-As-Pb is fundamental to be able to characterize the domains and to make an optimal classification of the geological material for its shipment to the metallurgical plant. The knowledge of the spatial distribution of the zinc and the Cu-Mo-Fe-As-Pb elements gives a broader view of the location of the zones of greater concentration of each element in order to make a better estimation of mining resources.